AI and Human Rights: Balancing Innovation with Social Justice in the Digital Era (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
Artificial Intelligence (AI) is transforming societies through automation, predictive analytics, and data-driven governance. However, as its influence expands, so do the concerns regarding human rights violations such as discrimination, privacy invasion, and digital exclusion. This paper investigates the relationship between AI innovation and the protection of human rights, emphasizing the need for ethical governance that harmonizes technological progress with social justice. Using a mixed-method research approach— including literature review, policy analysis, data evaluation, and case studies— this study reveals that while AI can promote fairness and inclusion, it can also perpetuate systemic bias if left unregulated. The research concludes that a rights-based AI governance framework—founded on transparency, accountability, inclusivity, and equality—is essential to ensure AI benefits all of humanity without reinforcing social disparities.